Pengaruh Pendapatan Asli Daerah (PAD) terhadap Kemandirian Keuangan Daerah Pemerintah Kota Bandung - Dian Novianti; Jouzar Farouq Ishak (Indonesian Accounting Research Journal, 2022)
Regional Financial Independence indicates the ability of the Regional Government to finance its own government activities through the Regional Original Income (PAD) consisting of Regional Taxes, Regional Levies, Separated Regional Wealth Management Results, and Other Legitimate PAD. The purpose of this study was to determine the effect of the four elements of PAD, either partially or simultaneously on the Regional Financial Independence of the Bandung City Government in 2016-2020. The data analysis technique used in this study is multiple linear regression analysis using SPSS version 26. The results of hypothesis testing state that partially Regional Taxes and Other Legitimate PAD have a significant positive effect on Regional Financial Independence, Regional Levies partially have a significant negative effect on Regional Financial Independence, while the results of Separated Regional Wealth Management Results have no significant effect on Independence Regional Finance. Simultaneously, Regional Original Income has a significant positive effect on Regional Financial Independence.